Aberrant regulation of the GSK‐3β/NRF2 axis unveils a novel therapy for adrenoleukodystrophy - Pablo Ranea‐Robles; Nathalie Launay; Montserrat Ruiz; Noel Ylagan Calingasan; Magali Dumont; Alba Naudí; Manuel Portero‐Otín; Reinald Pamplona; Isidre Ferrer; M Flint Beal; Stéphane Fourcade; Aurora Pujol (EMBO Molecular Medicine)
Abstract The nuclear factor erythroid 2‐like 2 (NRF2) is the master regulator of endogenous antioxidant responses. Oxidative damage is a shared and early‐appearing feature in X‐linked adrenoleukodystrophy (X‐ALD) patients and the mouse model (Abcd1 null mouse). This rare neurometabolic disease is caused by the loss of function of the peroxisomal transporter ABCD1, leading to an accumulation of very long‐chain fatty acids and the induction of reactive oxygen species of mitochondrial origin. Here, we identify an impaired NRF2 response caused by aberrant activity of GSK‐3β. We find that GSK‐3β inhibitors can significantly reactivate the blunted NRF2 response in patients’ fibroblasts. In the mouse models (Abcd1− and Abcd1−/Abcd2−/− mice), oral administration of dimethyl fumarate (DMF/BG12/Tecfidera), an NRF2 activator in use for multiple sclerosis, normalized (i) mitochondrial depletion, (ii) bioenergetic failure, (iii) oxidative damage, and (iv) inflammation, highlighting an intricate cross‐talk governing energetic and redox homeostasis in X‐ALD. Importantly, DMF halted axonal degeneration and locomotor disability suggesting that therapies activating NRF2 hold therapeutic potential for X‐ALD and other axonopathies with impaired GSK‐3β/NRF2 axis.